2017
DOI: 10.1080/0284186x.2017.1310394
|View full text |Cite
|
Sign up to set email alerts
|

Oncologists and hematologists’ perceptions of fertility-related communication – a nationwide survey

Abstract: Background: Despite the negative impacts of several cancer treatments on fertility, many patients do not recall having fertility-related discussions with their physicians. This study was conducted to identify those factors related to physicians' discussing the treatment impacts on fertility with cancer patients of reproductive age. Material and methods: In this nationwide survey of cancer care physicians (n ¼ 329, response rate 55%), oncologists and hematologists (mainly) completed a questionnaire on practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…In addition, having used FP seems to help both men (Armuand et al, 2015) and women (Corney & Swinglehurst, 2014) to be less troubled with concerns about their future fertility. The need to start treatment immediately has been reported to be a common reason for omitting fertility discussions in cancer care, especially with regard to women (Forman, Anders, & Behera, 2010;Micaux Obol et al, 2017;Ussher et al, 2016). In Sweden, all patients who receive treatment with a possible negative impact on fertility may undergo FP after evaluation, and the costs for the procedure are covered by the tax-funded health care.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, having used FP seems to help both men (Armuand et al, 2015) and women (Corney & Swinglehurst, 2014) to be less troubled with concerns about their future fertility. The need to start treatment immediately has been reported to be a common reason for omitting fertility discussions in cancer care, especially with regard to women (Forman, Anders, & Behera, 2010;Micaux Obol et al, 2017;Ussher et al, 2016). In Sweden, all patients who receive treatment with a possible negative impact on fertility may undergo FP after evaluation, and the costs for the procedure are covered by the tax-funded health care.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have investigated physicians' perspectives of FP care with focus on attitudes and barriers related to discussing impact on fertility and FP, experiences of discussing FP with patients and parents, and knowledge about FP . Recently, three literature reviews, covering 59 papers published between 2003 and 2016, presented consistent results regarding physicians' perspectives and challenges related to FP care involving both internal and external factors.…”
Section: Physicians' Perspectives and Challengesmentioning
confidence: 99%
“…Results reveal that oncologists frequently report a lack of knowledge of treatment‐induced fertility impairments and FP procedures, especially regarding the options for girls and young women, as a barrier for communicating fertility with patients and families . Micaux Obol and co‐workers investigated factors associated with discussing fertility with adult patients and found that physicians' experience of working in cancer care contributed statistically significantly to discussing fertility . Oncologists and hematologists who had worked in the field less than 5 years, and those who saw few patients of reproductive age per week, were less likely to discuss fertility issues with their patients .…”
Section: Physicians' Perspectives and Challengesmentioning
confidence: 99%
See 2 more Smart Citations